The integration of instruction strategies into an e-learning environment - Caniels, Marjolein [Verfasser]; Smeets-Verstraeten, Anke [Verfasser] (My University, 2009)
"This article gives a practical illustration of how several instruction strategies can be integrated into an e-learning environment. Further, it points out issues that should be addressed by an e-learning application, to increase efficiency in the workflow of all actors involved in student education." The approach presented in this paper has been applied in a newly developed learning content management system called "Sophia". (Autorenreferat, BIBB-Doku)
Keywords: L 4.2.2 Klassisches Fernlernen; L 4.2.3 Internetbasiertes Lernen / E-Learning; S 1.3.3 Vollzeitschulische Berufsausbildung; I 2.2.1 Westeuropa; Fernunterricht; E-Learning; Didaktik; Lernarrangement; Lernplattform; Schulische Berufsausbildung; Niederlande